Beispiel Nr: 15
$ \text{Gegeben:} \\ a1 \cdot x +b1 \cdot y =c1\\ a2 \cdot x +b2 \cdot y =c2 \\ \\ \text{Gesucht:} \\\text{x und y} \\ \\ \textbf{Gegeben:} \\ \\ 1x +2y =-4\\ -1x +2y = 5 \\ \\ \\ \\ \textbf{Rechnung:} \\\begin{array}{l|l} \begin{array}{l} I \qquad 1 x +2 y =-4\\ II \qquad -1 x +2 y = 5 \\ \text{I nach x auflösen}\\ 1 x +2 y =-4 \\ 1 x +2 y =-4 \qquad /-2 y\\ 1 x =-4 -2 y \qquad /:1 \\ x =-4 -2 y \\ \text{I in II}\\ -1 (-4 -2 y ) + 2 y = 5 \\ 4 +2 y +2 y = 5 \qquad / -4 \\ +2 y +2 y = 5 -4 \\ 4 y = 1 \qquad /:4 \\ y = \frac{1}{4} \\ y=\frac{1}{4} \\ x =-4 -2 y \\ x =-4 -2 \cdot \frac{1}{4} \\ x=-4\frac{1}{2} \\ L=\{-4\frac{1}{2}/\frac{1}{4}\} \end{array} & \begin{array}{l} I \qquad 1 x +2 y =-4\\ II \qquad -1 x +2 y = 5 \\ \text{I nach y auflösen}\\ 1 x +2 y =-4 \\ 1 x +2 y =-4 \qquad /-1 x\\ 2 y =-4 -1x \qquad /:2 \\ y =-2 -\frac{1}{2}x \\ \text{I in II}\\ -1x + 2(-2 -\frac{1}{2} x ) = 5 \\ -4 -1 x +2 x = 5 \qquad / -\left(-4\right) \\ -1 x +2 x = 5 -\left(-4\right) \\ -2 x = 9 \qquad /:\left(-2\right) \\ x = \frac{9}{-2} \\ x=-4\frac{1}{2} \\ y =-2 -\frac{1}{2} x \\ y =-2 -\frac{1}{2} \cdot \left(-4\frac{1}{2}\right) \\ y=\frac{1}{4} \\ L=\{-4\frac{1}{2}/\frac{1}{4}\} \end{array} \end{array} $